ANALISIS PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA KARYAWAN BAGIAN LOGISTIC PT. SEMARANG AUTOCOMP MANUFACTURING INDONESIA - Mahardhika, Renditya Leo; Salsiyah, Sri Marheni; Zaenuddin, Achmad - (Politeknik Negeri Semarang, 2015)
This study aims to determine: 1) whetherthe compensation and work environment hasa positive and significant impact onemployee motivation in logistic departmentof PT. Semarang Autocomp ManufacturingIndonesia (SAMI) Semarang, and 2) themost significant factors that affectcompensation and work environmenttowards employee motivation in logisticdepartment.In this study the author deploys 55questionnaires to all employees of thelogistic department at PT SAMI. The methodused by the authors is the classicalassumption test, multiple linear regressionanalysis and coefficient determination test.Based on the calculation of data andanalysis used, the regression equation is:Y = 0.881 + 0,315X1 + 0,297X2By using multiple linear regressionanalysis, it can be seen that the variablecompensation (X1) with the calculated valueof 5.579 T is greater than 1,675 tables T,and the significant value of 0.000 using a0.05 significances. 0.000 <0.05. It meansthat the compensation variable havesignificant and positive effect on workmotivation.There is a positive and significantinfluence between work environmentvariables (X2) on work motivation. With thevalue of T calculated = 3.683 (greater thanT table 1.675) and significance value of0.001 (less than 0.05).Based on the double determination test withadjusted R-square value of 0.573, this meansthat the variable compensation (X1) andwork environment (X2) has a 57.3% effecton work motivation.From the above results it is concludedthat the compensation and workenvironment have positive and significanteffect on work motivation variable.Compensation has a greater influence thanthe working environment. It can be seenfrom the t table, where the value ofcompensation = 5.579 which is greater than3,683 working environment.